Papillary cystic tumors of pancreas: A case report - PEREK, Sadık; PEREK, Asiye; ŞARMAN, Kemal; ERENLER KILIÇ, İlknur and ANDİCAN, A. Ahad (Cerrahpaşa Medical Journal, 2014)
Papillary cystic tumor of the pancreas is very rare, slow-growing tumor with low malignant potential. It occurs predominantly in young females. Preoperative diagnosis is difficult because of similarity with other cystic pancreatic lesions. Here, a female patient presented with nausea, malaise and abdominal and back pain, and a large mass in the abdomen.The CT scan of the abdomen demonstrated the mass in the head of the pancreas and she underwent a Whipple procedure. Histopathologically the mass was diagnosed as papillary cystic tumor of pancreas (PCTP). Here we report the case and discuss the characteristics of these tumors in the light of the literature.